PRILAKU PENGHIMPUNAN DANA MASYARAKAT OLEH PERBANKAN DI INDONESIA - Diah Wahyuningsih (MediaTrend, 2009)
This research aims to analyse behaviour of fund accumulation from community ini Indonesia using dynamic model. The result shows that, in long term case, domestic real interest rates significantly affects community fund accumulation by Indonesian banking, while in short term the influence is not significant. International interest rate has no significant influence on the accumulation of community fund by Indonesian banking either in long term or in short term. Indonesian income per capita has significant influence on community fund accumulation by Indonesian banking either in short or in long term.